Clinicoradiologic Evaluation of Eagle’s Syndrome and its Management - Pokharel, M; Karki, S; Shrestha, I; Shrestha, BL; Khanal, K; Amatya, RCM (Kathmandu University Medical Journal, 2015)
Background Eagle’s syndrome (Elongated styloid process) is often misdiagnosed due to its vague symptomatology. The diagnosis relies on detail history taking, palpation of styloid process in tonsillar fossa and imaging modalities.Objective To assess the length and medial angulation of elongated styloid process with the help of three dimensional computed tomography (3D CT) scan and to describe our clinical and surgical experience with patients suffering from Eagle’s syndrome.Method Prospective, analytical study conducted from August 2011 to August 2012 among 39 patients with Eagle’s syndrome. Detailed history taking, clinical examination and 3D CT scan was performed. Length and medial angulation was calculated. Patients with styloid process length longer than 2.50 cm underwent surgical excision via intraoral approach. Medial angulation of styloid process on both sides was correlated with each other using rank correlation coefficient. Wilcoxon Signed Rank test was applied to test significant difference between pre-operative and post-operative symptoms scores.Result Significant positive correlation was found between the medial angulation of styloid process on right side and left side (? =0.81, p